IMPLEMENTASI METODE WAFA DALAM MENINGKATKAN KUALITAS BACAAN AL –QUR’AN DI RUMAH SYAAMIL QUR’AN DI PONOROGO - Hevy Arum Sari; Nuraini Nuraini; Nurul Abidin (TARBAWI:Journal on Islamic Education, 2021)
Reading Al-Quran is important for a mother, remembering that Al-Quran source of teaching and way of life for Muslims, inside it load all of needed every human. This research used qualitative method that describing a thing by analyzed. The type of this research is field research that exixting database research. Data collection techniques done by observation, interview, and documentation. Output of this research show that 1) Implementation Wafa method inside improve quality reading Al-Qur’an in Syamil Qur’an Ponorogo home using with Hijaz song, with red colour as mark difference reading, and repeating readers is applied so well, start from plan process untuk realization. 2) Result inside implementation Wafa method for improving quality reading Quran in Syaamil Qur’an Ponorogo home produce result a) Knowledge, b) comprehension, c) skill. 3) A retard factor in Syaamil Qur’an Ponorogo home have same factors that is standart process of teaching obstacle in syaamil Qur’an Ponorogo home: 1. (a) emotional factor, (b) presence factor, (c) endless administration factor: 2. Supporting factor inside implementation Wafa method in Syaamil Qur’a Ponorogo home, (a) well graduation standard, (b) teaching standard, (c) infrastructure facilities, (d) standard financing